Dermatological clues to neurological diagnoses. - Warburton, K; Wakerley, B (2011)
Many neurological conditions are accompanied by skin changes, which frequently appear before the onset of the neurological symptoms. In some cases a rash may herald the start of an infectious process. In others, skin changes may mirror pathological processes that are also occurring in the brain or peripheral nerves. Careful examination of the skin can therefore provide important clues when making a neurological diagnosis, allowing early treatment and avoiding unnecessary tests. Instead of presenting an exhaustive list of cutaneous manifestation of every neurological condition, we aim to provide practical knowledge for the non-dermatologist to aid neurological differential diagnosis. We highlight the more common skin changes that occur in association with stroke, peripheral neuropathy, meningitis, encephalitis, malignancy and HIV. In addition, we cover the most frequently encountered neurocutaneous conditions and finally, we will remind the reader of skin changes associated with adverse reactions to drugs commonly used by neurologists.